The healing power of Camellia japonica L.: how flower types influence urban residents’ physiological and psychological wellbeing - Ai, Lijiao; Wang, Huan; Feng, Yilong; Li, Ting; Li, Zezhou; Zou, Min; Zhang, Qiaoyong (Frontiers in Psychology, 2025)
Color and form are closely related to our daily lives and can directly and rapidly affect people’s emotions, and it is of great significance to study the effects of color and form of garden plants on the body and mind of urban residents. In this study, the shrub Camellia japonica L., which has rich germplasm resources, was selected as the research object. It aims to address the following research questions: how flower colors and flower types of Camellia japonica L. affect human physiology and psychology? In this study, we recruited 158 participants to participate in a controlled experiment to quantitatively measure and analyze physiological (heart rate, blood pressure, oxygen saturation, electroencephalogram [EEG]) and psychological (anger, panic, nervousness, energy, fatigue, depression, and self-esteem) indices before and after viewing pictures of Camellia japonica L. of all colors and flower types, as well as of them in different colony configurations. The results of evaluating physiological indexes and POMS values showed that different types of Camellia japonica L. images had different restorative benefits. From the physiological indicators, blood pressure metrics were more sensitive as an evaluation of recovery effects than those of heart rate and oxygen saturation, and stress recovery was more significant after color stimulation than petal category and landscape type. Color, petal type, and landscape configuration type affect relaxation, concentration restoration, and other moods differently reflected by α wave and β wave of EEG. POMS questionnaires showed that viewing different types of picture processes of Camellia sinensis significantly reduced nervousness, anger, fatigue, depression, panic, and self-esteem, and the effect was significant in males than in females. Our findings provide a theoretical basis and selection for the garden application of Camellia japonica L. in a broader sense, intending to improve their health benefits and maximize the restorative effects of urban environments.